SEMINAR PEMBELAJARAN CORELDRAW DALAM MENINGKATKAN KOMPETENSI DESAIN GRAFIS , POSTER DAN PAMFLET DI SMP NEGERI 1 ARJASA SUMENEP - Zaehol Fatah; Hilma Aufini (CV. Denasya Smart Publisher, 2026)
Digital literacy and visual communication skills have become essential competencies in the 21st century. However, preliminary observations at SMP Negeri 1 Arjasa Sumenep indicated that students' competencies in designing visual communication media, particularly posters and pamphlets, remained low. This research aims to improve students' graphic design competencies through the implementation of CorelDraw software-based learning. The research method used was Classroom Action Research (CAR), consisting of two cycles that involved planning, action, observation, and reflection. The subjects of the research were eighth-grade students. Data collection instruments included practical design tests and observation sheets. The results showed an increase in the average score of design practicals from 58 in the pre-cycle stage to 74 in Cycle I , and increasing to 87 in Cycle II. In conclusion, structured learning using CorelDraw has proven to significantly improve the psychomotor skills and visual creativity of students at SMP Negeri 1 Arjasa Sumenep.